Quinoxaline 1,4-Dioxides: Advances in Chemistry and Chemotherapeutic Drug Development - Galina I. Buravchenko; Andrey E. Shchekotikhin (MDPI AG, 2023)
N-Oxides of heterocyclic compounds are the focus of medical chemistry due to their diverse biological properties. The high reactivity and tendency to undergo various rearrangements have piqued the interest of synthetic chemists in heterocycles with N-oxide fragments. Quinoxaline 1,4-dioxides are an example of an important class of heterocyclic N-oxides, whose wide range of biological activity determines the prospects of their practical use in the development of drugs of various pharmaceutical groups. Derivatives from this series have found application in the clinic as antibacterial drugs and are used in agriculture. Quinoxaline 1,4-dioxides present a promising class for the development of new drugs targeting bacterial infections, oncological diseases, malaria, trypanosomiasis, leishmaniasis, and amoebiasis. The review considers the most important methods for the synthesis and key directions in the chemical modification of quinoxaline 1,4-dioxide derivatives, analyzes their biological properties, and evaluates the prospects for the practical application of the most interesting compounds.